The features of establishing business universities and their importance (Journal of Educational Sciences, 2021)
In this article, using the classic example of the Silicon Valley (US) formation, as well as other foreign universities, the experience and models of entrepreneurial universities are analyzed; also, their defini- tion, evolution and genesis are presented. This research considers the model of the “triple helix”, which is based on the idea of knowledge formation in collaboration of universities with the authorities, and the subsequent transfer of technologies through cooperation between universities and business. The place of research universities in the formation of the triple helix model, as well as their role in the development of high-tech industries and applied research, has been determined.The research highlights the special role of research universities in the innovation system. In addi- tion, the research considers a gradual transition of bilateral relations “university-enterprise” and “state- university” to the “triple helix”.The existing experience in the development of entrepreneurial universities in Russia and Kazakhstan was also studied.Key words: «Triple Helix», entrepreneurial university, technology transfer, university ecosystem, entrepreneurial education.